(3GdGVWQGHGJ GdfaSjI h GdYbdjI h GdSdhcjIs (3GdhHGFjGJ (B- (3GdJYQja (B- (3eMGcGJ GdJTNjU (B- (3GdCSHGH (B- (3GdYdGL (B- (3GdeBd hGdeSGQs - (3ZGfe, eMeO MSfs ((3GdbGgQIs (3ecJHI GdGfLdh GdeUQjIs, 2006)
(3jJfGhd GdcJGH GdYOjO ef GdGVWQGjGJ GdfaSjI hGdYbdjI hGdSdhcjI eKd Gdbdb hCfhGYg GdGcJFGH hGdaUGe hGdghS GdGfMQGaGJ GdLfSjI (B-(3GVWQHGJ Gdfhe(B-(3GVWQGHGJ GdaUGe hZjQgG ,, Ke JfGhd cd GVWQGH ef GdGVWQGHGJ GdSGHbI ef MjK hHGFjGJ GdGfJTGQ (B-(3GdJYQja HGdGVWQGHGJ eMcGJ GdJTNjUs
(3jJfGhd GdcJGH GdYOjO ef GdGVWQGHGJ GdfaSjI h GdYbdjI h GdSdhcjI eKd Gdbdb h CfhGYg, GdGcJFGH h GdaUGe hGdghS, GdGfMQGaGJ GdLfSjI GVWQGHGJ GdTNUjI, GdGYJeGO Ydi GdeNOQGJ, GVWQGHGJ Gdfhe h GVWQGHGJ GdaUGes
(3eJGM efg WHYI (B2014(3h (B2015 (3HecJHI GdRGhjI GdMeQGAs
1 8 9 13
Keywords: (3GdCcJFGHs; (3GdCeQGV GdfaSjIs; (3GdGVWQGHGJ GdLfSjIs; (3GdGVWQGHGJ GdYbdjIs; (3GdGVWQGHGJ GdfaSjIs; (3GdPgGfs; (3GdUMI GdfaSjIs; (3GdaUGes; (3Gdbdbs; (3Gdbdbs